Advances in mode of action of antimalarials and resistance mechanisms 1 - Warhurst, David (Henry Stewart Talks, 2013)
Life cycle stage as drug target, Action of antiplasmodial drugs, The digestive vacuole, Resistance to sulfadoxine and pyrimethamine, Artemisinin mode of action